If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 72 + -7j = 72 Add '-72' to each side of the equation. 72 + -72 + -7j = 72 + -72 Combine like terms: 72 + -72 = 0 0 + -7j = 72 + -72 -7j = 72 + -72 Combine like terms: 72 + -72 = 0 -7j = 0 Solving -7j = 0 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Divide each side by '-7'. j = 0 Simplifying j = 0
| (x-6)(x+9)= | | 6x-5y=8 | | (m^2-7m-6)(7m^2-3m-7)= | | 4-5x=9x+18 | | 3-x=9-3x | | 14-6b=4b+34 | | 9-3s=4s+30 | | 135-5x=31x+23 | | 13-4y=2y-11 | | -2b+7-3n=2 | | 14x-10=166-38x | | (3x+5)(4x-1)= | | 2(x-5)-6(3x-1)+8=2(2x-8)-(3x+4-3) | | 7x-2=14+3x | | 7x+9-3x+2=5 | | 12x-5=8x+31 | | 500*1/2+70= | | 6x+10=2x+4 | | 8+4x=10x+6 | | x^2-60x+720=0 | | 8x+4=10x+6 | | 5-6x=6x+12 | | 3x+5=-75-10x | | e=70x+20y-50 | | (n+5)*7=49 | | (n-10)*3=21 | | 10x+6=8x+4 | | 25x=0 | | 0.6w-0.3w+0.2w=5 | | 12x-21=75 | | 122=n+98 | | 50=n-47 |